EBSD-based FEM simulation of residual stresses in a WC6wt.-%Co hardmetal. (June 2018) - Kayser, W.; Bezold, A.; Broeckmann, C.
Abstract: Tungsten carbide hardmetals are widely used in cutting, tooling, and wear based applications. During the cooling stage of liquid phase sintering, severe internal micro stresses form between carbide and binder. A detailed microstructural FEM model, capable of predicting these residual stresses accurately, has been developed on the basis of EBSD images of a WC6wt.-%Co hardmetal. This approach yields an extruded 2.5D model that is generated using 2D geometry information on the grains of each phase and the corresponding 3D grain-orientation data. The orientations of the carbides and the binder were detected using samples prepared by ion beam etching. The simulation approach presented, utilizes a temperature-dependent, isotropic elasto-viscoplastic constitutive description of the binder and a temperature-dependent, orthotropic elastic description of the carbides. Using these constitutive models, the type-II residual-stress response is calculated for the hardmetal microstructure. The temperature-dependent phase-averaged hydrostatic stresses, which are predicted by the model, are in good agreement with experimental neutron-diffraction data. Highlights: Temperature dependent simulation of residual stresses in cemented carbides. Implementation of visco-plastic binder behavior. Semi-automatic model generation based on EBSD-Data.